Mechanical energetic processes during the giant swing exercise before dismounts and flight elements on the high bar and the uneven parallel bars - Arampatzis, A.; Brüggemann, G. P. (Journal of Biomechanics, 1999)
The purposes of this study were as follows: (1) To study the energy exchange between the body of the gymnast and the high bar and uneven parallel bars during forward and backward giant swings. (2) To examine the differences between the mechanical energy produced and the mechanical energy absorbed by the muscles during forward and backward giant swings on the high bar and the uneven parallel bars. The data were gathered during the gymnastic world championships in 1994. The experimental set up consisted of two video cameras (50 Hz) and two force measurement bars (500 Hz). A total of 101 giant swings before dismounts and flight elements performed by 33 male and 34 female gymnasts were analyzed. There are characteristically two main phases during forward and backward giant swings before dismounts and flight elements. During the first phase energy is transferred from the gymnast's body into the bar. During this phase of the backward giant swing the energy of the system decreases because the amount of energy decrease of the gymnast's body is more than the energy transferred into the high bar. An exception can be seen during the giant swings in which the gymnast used the power technique. During forward giant swings the energy of the system increases during the first phase. This occurs through active flexion of the hip joint which produced the extra muscular energy. During the second phase energy is transferred from the bar back into the gymnast's body whose total energy increases. An increase in the energy of the system can only be achieved through muscular work. During the second phase of the backward giant swing the energy of the system increases. The forward giant swings performed on the uneven parallel bars showed a large energy loss during this phase. The energy deficit seen during the first phase of the backward giant swing can be improved by using the power technique. To achieve this the athlete must be in a bent position at the start of the giant swing exercise. Through extension at the shoulder and hip joints muscular energy can be put into the system.